Immuno-modulating Properties of Aloe Vera and its Efficacy in Immune Mediated Disorders - Jahan, Sarwat (International Journal of Pathology, 2022)
Introduction: Aloe produces immune-modulation as it can suppress as well as stimulate the selected sites of the immune system at the same time. The polysaccharide gets attached to the receptors for macrophages that lead to the stimulation of cytokine production. In addition, there is activation of cell mediated immune response too. Aloe has been noted to increase the peripheral percentage of CD4 and CD8 cells, activation of the NF-κB protein and stimulation of interleukin production. Methodology: In this cross-sectional survey, literature was searched using two search engines: Pubmed and Google Scholar. Pubmed using MesH terms was used as the first option for validation of the systematic review process and the process was further refined using google scholar Result: Immune-modulation by aloe results from its effect on the T cells, complement system, cytokines as well as the No synthesis. The modulation can be used as a therapeutic benefit for disorders triggered by an abnormal immune response e.g., multiple sclerosis, hyperthyroidism, psoriasis, lichen planus etc. Conclusion: The efficacy and utility of aloe in auto-immune disorders offers promising range of properties that may help improve the treatment outcomes of immune mediated disorders